2022
DOI: 10.17942/sted.1149434
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Women's Awareness Levels of Domestic Violence

Abstract: Objective: The study was conducted to examine the awareness levels of women about domestic violence. Material and Method: The population of the descriptive study consists of women between the ages of 18-65 residing in Artvin and Osmaniye. The study was completed with 433 participants who met the research criteria. The data were collected using the “Sociodemographic Data Form” and the “Domestic Violence Awareness Scale”. Findings: 37,9% of the participants were exposed to family violence. Women repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Contrary to these studies, different studies reported that primary school graduate women had higher awareness of domestic violence (Ataman et al, 2022), and women with higher education levels were more exposed to violence (Kocacık & Çağlayandereli, 2009). It can be asserted that these different results were caused the different samples used in the studies.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Contrary to these studies, different studies reported that primary school graduate women had higher awareness of domestic violence (Ataman et al, 2022), and women with higher education levels were more exposed to violence (Kocacık & Çağlayandereli, 2009). It can be asserted that these different results were caused the different samples used in the studies.…”
Section: Discussionmentioning
confidence: 96%
“…Different studies on domestic violence awareness reported that individuals at later ages defined the domestic violence more accurately (Özgür et al, 2011; Özyürek & Kurnaz, 2019). In their study, Ataman et al, observed that the awareness of domestic violence was higher among women who were over 45 years old (Ataman et al, 2022). It was determined that individuals having bachelor's and postgraduate degrees had a lower mean score than the others.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation